Improving Dissolution Performance and Drug Loading of Amorphous Dispersions Through a Hierarchical Particle Approach - Hiew, Tze Ning; Saboo, Sugandha; Zemlyanov, Dmitry Y.; Punia, Ashish; Wang, Michael; Smith, Daniel; Lowinger, Michael; Solomos, Marina A.; Schenck, Luke; Taylor, Lynne S. (Journal of pharmaceutical sciences, 2023)
Co-precipitation is an emerging manufacturing strategy for amorphous solid dispersions (ASDs). Herein, the interplay between processing conditions, surface composition, and release performance was evaluated using grazoprevir and hypromellose acetate succinate as the model drug and polymer, respectively. Co-precipitated amorphous dispersion (cPAD) particles were produced in the presence and absence of an additional polymer that was either dissolved or dispersed in the anti-solvent. This additional polymer in the anti-solvent was deposited on the surfaces of the cPAD particles during isolation and drying to create hierarchical particles, which we define here as a core ASD particle with an additional water soluble component that is coating the particle surfaces. The resultant hierarchical particles were characterized using X-ray powder diffraction, differential scanning calorimetry, scanning electron microscopy, and X-ray photoelectron spectroscopy (XPS). Release performance was evaluated using a two-stage dissolution test. XPS analysis revealed a trend whereby cPAD particles with a lower surface drug concentration showed improved release relative to particles with a higher surface drug concentration, for nominally similar drug loadings. This surface drug concentration could be impacted by whether the secondary polymer was dissolved in the anti-solvent or dispersed in the anti-solvent prior to isolating final dried hierarchical cPAD powders. Grazoprevir exposure in dogs was higher when the hierarchical cPAD was dosed, with ∼1.8 fold increase in AUC compared to the binary cPAD. These observations highlight the important interplay between processing conditions and ASD performance in the context of cPAD particles and illustrate a hierarchical particle design as a successful approach to alter ASD surface chemistry to improve dissolution performance. [Display omitted]